Resource savings in the context of innovative development of the city communal econome (Economics and region, 2018)
The article deals with resource savings in utilities sector cities, sources of financing of innovation activity. There are formulated approaches to strategic management innovative development utilities, processes resource savings in the context of innovation development. The author proposed financial incentive tools resource savings in public services communal economy of cities
Keywords: resource savings; innovative development; communal economy of the city; financial incentive tools resource savings